Influence of dietary condition on the ratio of the compounds emitted by larvae Chilecomadia valdiviana (Lepidoptera: Cossidae) - Reyes-García, Luis (2020)
Chilecomadia valdiviana (Lepidoptera, Cossidae), locally known as "Gusano del Tebo", is a polyphagous pest that, in its larval stage, feeds on the wood of the host species. C. valdiviana is distributed in the southern region of Chile and Argentina and its larvae mainly attack eucalyptus and fruit trees. Previous research has reported the identification of the volatile compounds produced by this species in its larval stage. In this work, the effects of two dietary conditions on these volatile compounds were described: groups of individuals fed with wood vs. others without food. The results obtained provide empirical evidence that C. valdiviana modulates the emission of the compounds according to the effect of stimulus.